THE EFFECT OF WORK FROM HOME ON EMPLOYEE PRODUCTIVITY IN BANKING INDUSTRY - Prasetyaningtyas, Sekar Wulan; Heryanto, Clivensen; Nurfauzi, Nadia Fasha; Tanjung, Sugiharto Bangsawan (Jurnal Aplikasi Manajemen, 2021)
Recent COVID-19 Pandemic has forced many institutions to adopt work from home (WFH) practice whether they’re ready or not. Conditions affecting knowledge worker productivity while adopting new WFH practices become increasingly relevant as companies adapt to the new normal era. This study investigates the direct impact of WFH on productivity and the mediating impact of WFH on productivity through work life balance (WLB) and job satisfaction in the banking industry located in the Greater Jakarta Area. As such, questionnaires were conducted with 234 respondents who have experience of the WFH program due to COVID-19 pandemic and working in the banking industry located in the Greater Jakarta Area. Findings revealed how job satisfaction is a mediating variable between WFH and Productivity, and WFH positively impacts overall productivity. However, contrary to our predictions, results also showed that WFH has a negative impact on WLB. Further research can extend the proposed model of this study by considering adding several variables which might affect productivity in WFH arrangements or implement the already proposed model to other industries.